(untitled) (Research, Society and Development, 2023)
The Tax on Urban Property and Territorial Property – IPTU, which is the responsibility of the municipalities, brings with it a responsibility for the municipal public management in relation to the collection and allocation of its revenue. The present work aims to analyze the effectiveness of IPTU collection in relation to the perspective of application of its revenue. For this purpose, a qualitative, exploratory research was carried out in relation to its objectives. The objects of the study were the municipal tax area, its legal instruments and the collection behavior, as well as subsidies for the improvement of tax management in municipal management. For data analysis, the technique of the inductive method was applied. The main results obtained show that municipal management needs to improve in terms of updating its legislation, as well as improving the revenue collected with IPTU. When comparing the expense with the allocation of amounts collected in the last three years, it was noticed that the revenue is still very low. In addition, regarding the destination of IPTU revenue, there is a constitutional and infraconstitutional provision regarding its specific destination, as well as percentages that can be used for any expense.